Inflammatory-nutritional duality of NPAR: a novel biomarker for early prediction of acute liver injury in acute myocardial infarction complicated by type 2 diabetes mellitus - Huang, Xiaorui; Lian, Zizhu; Qi, Shanshan; Yu, Hang (Frontiers in Pharmacology, 2025)
Background/ObjectivesAcute liver injury (ALI) is a severe complication of acute myocardial infarction (AMI) comorbid with type 2 diabetes mellitus (T2DM), serving as an independent risk factor for adverse prognosis and imposing a significant disease burden. The aim of this study was to identify predictive value of a composite of inflammation and nutrition-related indicators for the risk of ALI in AMI patients comorbid with T2DM.MethodsAMI patients with T2DM hospitalized at the First Affiliated Hospital of Xi’an Jiaotong University between January 2018 and May 2025 were included. Clinical data and medication information were collected through the hospital’s biospecimen information resource center. The patients enrolled were divided into non-hepatic injury group, mild hepatic injury group and moderate-to-severe hepatic injury group according to the alanine transaminase (ALT) level tested during hospitalization. Neutrophil percentage-to-albumin ratio (NPAR) was calculated as the ratio of neutrophil percentage (NP) to serum albumin (ALB) level (NPAR = NP/ALB). The primary outcome is acute liver injury during hospitalization.ResultsAmong 5133 AMI patients with T2DM (76.57% male, median age 62.61 years (51.29–72.93), acute liver injury occurred in 7.60% (n = 390) of the cohort and moderate-to-severe hepatic injury occurred in 1.34% (n = 69). Compared with non - hepatic injury, mild (60.7% vs. 45.2%, P < 0.001) and moderate-to-severe hepatic injury (65.2% vs. 45.2%, P < 0.001) had higher ST - segment elevation myocardial infarction (STEMI) rates. Both hepatic injury subgroups showed higher Killip III/IV prevalence (mild: 26.2% vs. 8.7%, moderate-to-severe: 53.6% vs. 8.7%, both P < 0.001). Moderate-to-severe vs. mild injury had older age (69.50 ± 11.79 vs. 64.35 ± 11.77, P < 0.05) and more arrhythmias (46.4% vs. 27.1%, P < 0.001). After adjustment, NPAR independently predicted ALI (OR = 1.70, 95% CI: 1.33–2.17) and moderate-to-severe injury (OR = 2.90, 95% CI: 1.90–4.42), with an AUC of 0.86 (95% CI: 0.81–0.92) for moderate-to-severe injury. A history of cancer was an independent risk factor for ALI. Among these patients, NPAR demonstrated AUCs of 0.83 for overall ALI and 0.89 for moderate-to-severe ALI.ConclusionNPAR effectively predicts moderate-to-severe hepatic injury in AMI patients with T2DM, suggesting its potential as a clinically useful early marker. Furthermore, while cancer is an independent risk factor for ALI in this population, NPAR maintains strong predictive performance for ALI even in this high-risk subgroup.